OA5 Empowering ten culturally and linguistically diverse communities in melbourne, australia, to access culturally responsive palliative care. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Waanders, Odette; Kennedy, Michael; Paterson, Michelle; Radermacher, Harriet; Petreska, Elena; Timmins, Susan; Ferguson, Annmarie
Abstract : Background: This project addresses low levels of awareness and use of palliative care among ten culturally and linguistically diverse (CALD) communities in Melbourne, Australia. Aim: To increase awareness, understanding and use of palliative care among the Arabic speaking, Chinese, Croatian, Greek, Italian, Macedonian, Maltese, Polish, Turkish and Vietnamese communities in Melbourne and to strengthen the provision of culturally responsive palliative care. Method: In July 2013 the palliative care and ethnic peak bodies initiated a two-year project with 10 ethnic communities (5 per year) to deliver peer education sessions about palliative care in community languages. Adjunct activities include community engagement, relationship-building, media, cultural responsiveness education for palliative care services, and evaluation. Results: As at mid-July 2014, feedback from 837 participants (80% of 1050 attendees) at 37 community education sessions for 4 CALD communities indicated that 68% did not know about palliative care before the session. 90% had learnt new information, 90% had an intention to tell friends and family about palliative care and 90% thought palliative care was a good idea. Updated results will be provided. Conclusion: Participatory and engagement strategies are needed to improve awareness of palliative care among CALD communities. The formation of community reference groups is a valuable strategy that respects community leadership, expertise and networks. The participation of CALD communities in tailoring education and information to meet specific cultural, spiritual and linguistic needs is essential. The participation of palliative care services in project activities is valued and strengthens relationships of trust and understanding.